The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jbm4.10545
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Bone Quantity, Microarchitecture, and Collagen Cross‐links on Mechanics Following In Vivo Irradiation in Mice

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…For example, non‐enzymatic collagen cross‐links known as AGEs, which form along the collagen backbone due to radiation‐induced oxidation, ( 63,64 ) are elevated in the irradiated bone in the current study and in other preclinical irradiation models. ( 37,68,69 ) However, the significant increase in AGEs was not associated with the observed reductions in vertebral strength. This is consistent with previous work in our lab ( 21 ) and others, ( 37,69 ) which demonstrated that AGEs do not accumulate at concentrations sufficient to alter bone mechanical properties.…”
Section: Discussionmentioning
confidence: 92%
“…For example, non‐enzymatic collagen cross‐links known as AGEs, which form along the collagen backbone due to radiation‐induced oxidation, ( 63,64 ) are elevated in the irradiated bone in the current study and in other preclinical irradiation models. ( 37,68,69 ) However, the significant increase in AGEs was not associated with the observed reductions in vertebral strength. This is consistent with previous work in our lab ( 21 ) and others, ( 37,69 ) which demonstrated that AGEs do not accumulate at concentrations sufficient to alter bone mechanical properties.…”
Section: Discussionmentioning
confidence: 92%
“…Mouse micro-CT scans (Figure 1 ) were provided as a courtesy of Dr. Tony Keaveny of the University of California Berkeley, College of Engineering [ 13 ]. These scans were collected at the NASA Ames Research Center, and the collection was approved by the Institutional Animal Care and Use Committee under protocol #NAS‐13‐004‐Y3.…”
Section: Methodsmentioning
confidence: 99%